2004
DOI: 10.1677/joe.0.1810347
|View full text |Cite
|
Sign up to set email alerts
|

Brevinin-1 and multiple insulin-releasing peptides in the skin of the frog Rana palustris

Abstract: Few studies have comprehensively examined amphibian granular gland secretions for novel insulinotropic peptides. This study involved isolation and characterisation of biologically active peptides from the skin secretions of Rana palustris frogs. Crude secretions obtained by mild electrical stimulation from the dorsal skin surface were purified by reversed-phase HPLC on a semipreparative Vydac C18 column, yielding 80 fractions. These fractions were assayed for insulin-releasing activity using glucoseresponsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 29 publications
(39 reference statements)
0
25
0
Order By: Relevance
“…Recent studies have shown that several frog skin peptides that were first identified on the basis of their ability to inhibit the growth of bacteria also stimulate insulin release in vitro from BRIN‐BD11 rat clonal β ‐cells at low concentrations that are not cytotoxic to the cells. Such insulin‐releasing peptides have been identified in skin secretions and/or skin extracts from the species Hylarana güntheri [8], Lithobates catesbeianus [9], Lithobates palustris [10], Lithobates pipiens [11], Lithobates septentrionalis [12] and Pelophylax saharicus [13] belonging to the family Ranidae and from Hylomantis lemur [14] and Pseudis paradoxa [15] belonging to the family Hylidae. In addition, brevinin‐2GUb from H. güntheri [8], phylloseptin‐L2 from H. lemur [14] and brevinin‐2–related peptide (B2‐RP) from L. septentrionalis [12] have been shown to be active in vivo, increasing plasma insulin concentrations and improving glucose tolerance in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that several frog skin peptides that were first identified on the basis of their ability to inhibit the growth of bacteria also stimulate insulin release in vitro from BRIN‐BD11 rat clonal β ‐cells at low concentrations that are not cytotoxic to the cells. Such insulin‐releasing peptides have been identified in skin secretions and/or skin extracts from the species Hylarana güntheri [8], Lithobates catesbeianus [9], Lithobates palustris [10], Lithobates pipiens [11], Lithobates septentrionalis [12] and Pelophylax saharicus [13] belonging to the family Ranidae and from Hylomantis lemur [14] and Pseudis paradoxa [15] belonging to the family Hylidae. In addition, brevinin‐2GUb from H. güntheri [8], phylloseptin‐L2 from H. lemur [14] and brevinin‐2–related peptide (B2‐RP) from L. septentrionalis [12] have been shown to be active in vivo, increasing plasma insulin concentrations and improving glucose tolerance in mice.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of using amphibian skin as the object of investigation is the use of gentle methods (e.g. skin stimulation by norepinephrine (Mechkarska et al 2011) or gentle electrical stimulation (Marenah et al 2004) for sample preparation. Hence, there is no need to harm or kill animals for this work.…”
Section: Innothink Center For Research In Biomedical Innovation and Tmentioning
confidence: 99%
“…This new function may give an additional protection for frogs by stimulating insulin secretion and causing hypoglycaemia in attacking predators (Marenah et al 2004). …”
Section: Other Activities Of Brevininsmentioning
confidence: 99%
“…In particular, skin secretions may contain peptides with cytolytic properties that serve to protect the organism against invasion by bacteria, fungi and protozoa and to deter ingestion by predators [4,5]. Such insulin-releasing peptides have been identified in secretions from the frogs Phyllomedusa trinitatis [6], Agalychnis litodryas [7], Bombina variegata [8], Rana saharica [9], R. palustris [10], and R. pipiens [11]. Such insulin-releasing peptides have been identified in secretions from the frogs Phyllomedusa trinitatis [6], Agalychnis litodryas [7], Bombina variegata [8], Rana saharica [9], R. palustris [10], and R. pipiens [11].…”
Section: Introductionmentioning
confidence: 99%